"But it's a nice compromise" – Qualitative multi‐centre study of barriers and facilitators to acute telestroke cooperation in a regional stroke network. (28th October 2021) - Busetto, Loraine; Sert, Melek; Herzog, Franziska; Hoffmann, Johanna; Stang, Christina; Amiri, Hemasse; Seker, Fatih; Purrucker, Jan; Mundiyanapurath, Sibu; Ringleb, Peter Arthur; Nagel, Simon; Bendszus, Martin; et al.
Abstract: Background: Telemedical services can be used to complement on‐site services when demand for specialists exceeds supply or when specialists are not evenly distributed across health systems. Using stroke as an example, this study aimed to explore how patients and staff experience telestroke cooperation in a stroke network in Germany. Methods: We conducted a qualitative multi‐method and multi‐centre study combining 32 non‐participant observations at one hub and four spoke hospitals with 26 semi‐structured interviews with hub and spoke staff as well as stroke patients and relatives. Observation protocols and interview transcripts were analysed to identify barriers and facilitators to telestroke cooperation from the perspectives of staff, patients and relatives. Results: In terms of barriers to telestroke cooperation, we found technological problems, providing the treatment for one patient from two sites, competing priorities between telestroke and in‐house duties in the spoke hospitals, as well as difficulties in participating in the teleneurological examination via a videoconferencing system for older and disabled patients. In terms of facilitators, we found an overall very positive perception of telestroke provision by patients, good professional relationships within the network, and sharing of neurological expertise to be experienced as helpful for telestroke cooperation. Conclusions: We recommend better integration of telemedical services into the care pathway, fostering relationships within the network, improved technological support and resources, and more emphasis within networks, in public awareness efforts as well as in academia on the evaluation of telemedical services from the perspectives of patients and relatives, especially older patients and patients with disabilities. Abstract :